2008
DOI: 10.1007/s11207-008-9170-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bimodality in Histograms Formed from GALLEX and GNO Solar Neutrino Data

Abstract: Abstract.A histogram display of the solar neutrino capture-rate measurements made by the GALLEX experiment appears to be bimodal, but that of the follow-on GNO experiment does not. To assess the significance of these results, we introduce a "bimodality index" based on the probability-transform procedure. This confirms that the GALLEX measurements are indeed bimodal (at the 99.98 percent confidence level), and that the GNO measurements are not. Tracking the bimodality index as a function of time shows that the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…It has been known for some time that the published capture-rate measurements derived from the GALLEX solar neutrino experiment are bimodal in the sense that the histogram formed from these data has two distinct peaks (Sturrock and Scargle, 2001). We recently introduced a "bimodality index" to provide an objective measurement of bimodality (Sturrock, 2008). This analysis confirmed that the published capture rate measurements for the GALLEX experiment are indeed bimodal, but those for the GNO experiment are not.…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…It has been known for some time that the published capture-rate measurements derived from the GALLEX solar neutrino experiment are bimodal in the sense that the histogram formed from these data has two distinct peaks (Sturrock and Scargle, 2001). We recently introduced a "bimodality index" to provide an objective measurement of bimodality (Sturrock, 2008). This analysis confirmed that the published capture rate measurements for the GALLEX experiment are indeed bimodal, but those for the GNO experiment are not.…”
Section: Introductionsupporting
confidence: 58%
“…In order to assign a significance level to the bimodality of a histogram, we have recently introduced a "bimodality index" B (Sturrock, 2008). This index has the property that, if the neutrino flux is constant, we expect that B will be distributed exponentially so that the probability of obtaining the value B or more is e −B .…”
Section: Histogramsmentioning
confidence: 99%
“…However, fitting data can be difficult when their distribution is bimodal, which occurs commonly in practice: in astrophysics, the metallicity of the globular cluster system in the Milky Way (see [1]); in ecology, the tree cover of moist savanna and tropical forest ecosystems (see [2]); in genetics, gene expression measurements (see [3]). Other practical examples of bimodality in data can be seen in [4][5][6]. In the literature, there are many proposals discussing bimodal distributions; e.g., the works of [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%